Análisis Del Estrés Laboral Y Su Repercusión En La Salud Física Y Mental En Operadores De Tracto Camión - López-Trejo, Homero Janai; Carrera-Salazar, Claudia Olivia; Eurrieta-Ortiz, María Isela; García-Arroyo, Luz del Carmen; Gómez-Márquez, Montserrat; LLanillo-Navales, Jesús Gerardo; Marín-Ramos, Martha; Romo-Celis, Fernando Agustín; González-Pérez, Manuel (European Scientific Journal, ESJ, 2018)
The Work stress (WS) is one of the leading causes of deterioration of physical and psychological well-being within organizations. In this research the multivariate dependence of some signs and symptoms of work-related illness was analyzed and calculated. A cross-sectional and descriptive study of a base of logistic operations of fleet dedicated to the transportation of beer in the center of the state of Veracruz was carried out. The population studied was 230 operators. Only male operators, active within the company, were included and operators who at the time of the study were under medical and vacation disability were excluded. The multivariate Pearson correlation was used to validate the research questions and chi-square to calculate the dependence of variables. As a result, we obtained five variables taken from two in two that were dependent on each other. We conclude that there is a healthy relationship between the observed variables, which are listed in order of pathological impact and their physiological reexaminations in the organism. The pressure within work caused by job stress represents a potent source of mental illness such as depression.